Nutrition Supplementation and Education May Increase the Healing Rate in Diabetic Patients with Foot Ulcers (P19-005-19) - Basiri, Raedeh (Curr Dev Nutr, 2019)
OBJECTIVES: This study examined the effects of high protein dietary supplementation and nutrition education on the healing of diabetic foot ulcers. METHODS: Twenty-nine adults with diabetic foot ulcers were recruited from the Tallahassee Memorial Hospital Wound Care Clinic. Participants were randomly assigned to treatment (n = 15) or control (n = 14) group. The treatment group received two carbohydrate controlled high protein shakes to consume daily, and was educated regarding adequate intake of low-fat protein sources, fruits, vegetables, complex carbohydrates and minimizing simple carbohydrates. The control group did not receive any intervention. Daily supplementation provided a total of 500 kilocalories, 28 grams of high-quality protein, and approximately 50% of micronutrient requirements. Anthropometric measurements (weight, height, BMI) and wound planimetry were examined at baseline and every four weeks until the wound healed or up to 12 weeks. RESULTS: There was no significant difference between the groups at baseline for BMI (mean = 33.8 ± 7 kg/m(2)), age (mean = 53.34 ± 11.14 years), duration of diabetes (mean = 13 years), duration of wounds (mean 10.8 months) or wound area (mean = 450 mm(2)). Wound healing rate (decrease in the area of the wound/week) for the treatment group was three times faster than the control group (151.1 mm(2)/week vs. 45.2 mm(2)/week respectively). CONCLUSIONS: Improved nutritional intake using nutritional supplementation and patient education has a strong positive effect on the wound healing rate of diabetic foot ulcers. Faster wound healing improves quality of life and functionality of patients with diabetic foot ulcers. FUNDING SOURCES: Dissertation award.